SPECTROSCOPIC STUDY OF THE CHARGE TRANSFER COMPLEXES FOR SOME DYES - ABED AL-HAKIM DAHAM; SABRI M. HUSSEN (مجلة جامعة الانبار للعلوم الصرفة, 2012)
This research was included the spectrophotometric study of charge transfer complexes of Lawson dye ( as acceptor ) with nine compounds ( as donors ) at room temperature 255 c by using absolute ethanol as solvent . Formation constants Kc and molar absorptivity (ε) were calculated by using Benesi – Hildebrand equation and linear relation ship was obtained which indicated, clearly a 1:1 stoichiometric ratio of donor to acceptor . Isolation of solid complexes were successfully achieved by mixing equimolar quantities of donors with acceptor in ethanol as solvent . These complexes were identified by using some spectroscopic methods .From the results , it concluded clearly that electron density of donors and geometry were the fundamental factors , that effect to the stability of complex formed , that electron density of donors and geometry of complex played important roles in the value of Kc and stability of these complexes .